2016
DOI: 10.4103/0975-962x.189338
|View full text |Cite
|
Sign up to set email alerts
|

Erosive effects of pediatric liquid medicinal syrups on primary enamel: An in vitro comparative study

Abstract: Context:The use of liquid medicinal syrups in childhood is high owing to the reasons that children suffer from illness quite often. The acidic component in the formulations may cause erosion to the dental tissues.Aims:The aim of this study is to evaluate the erosive potential of pediatric liquid medicinal syrups on the deciduous teeth.Subjects and Methods:A total of sixty extracted/exfoliated noncarious deciduous molars were used. Four medical syrups were used (viz., 1 – artificial saliva [control], 2 – Ferium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 9 publications
(11 reference statements)
1
9
0
Order By: Relevance
“…In the current study, it was observed that all of the syrups used caused a significant decrease in the microhardness on all the days with a p value of <0.001 and also there is a difference in the values of microhardness in all the syrups on the same days also. This is in agreement with a study done by Kulkarni et al, where they have concluded that Ferium XT, Crocin syrup, and Ambrolite-D had a significant and gradual loss of surface microhardness on all days (7, 14, 21 and 28 days) [9].…”
Section: Discussionsupporting
confidence: 93%
“…In the current study, it was observed that all of the syrups used caused a significant decrease in the microhardness on all the days with a p value of <0.001 and also there is a difference in the values of microhardness in all the syrups on the same days also. This is in agreement with a study done by Kulkarni et al, where they have concluded that Ferium XT, Crocin syrup, and Ambrolite-D had a significant and gradual loss of surface microhardness on all days (7, 14, 21 and 28 days) [9].…”
Section: Discussionsupporting
confidence: 93%
“…Dental erosion is a chronic and localized pathological chemical process that causes irreparable and progressive loss of hard tooth structure due to acid dissolution without bacterial causes (1,2). It starts with softening of the enamel surface.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, their consequent harmful effects on oral structures are exacerbated by their long‐term use, leading to sustained negative outcomes. 2 …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, their consequent harmful effects on oral structures are exacerbated by their long-term use, leading to sustained negative outcomes. 2 Acid exposure leads to the progressive dissolution of minerals, which results in the loss of dental hard tissues. Therefore, the best way to prevent tooth erosion is to minimize the amount and frequency of contact with acidic syrups and suspensions routinely used by children for medical purposes, thereby increasing acid resistance by the remineralization of the enamel surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation